2004
DOI: 10.1093/gerona/59.9.m962
|View full text |Cite
|
Sign up to set email alerts
|

Old or Frail: What Tells Us More?

Abstract: Using frailty as the criterion to select older persons at risk for interventions may be better than selecting persons based only on their chronological age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
304
0
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(325 citation statements)
references
References 12 publications
6
304
0
15
Order By: Relevance
“…Frailty was measured in both studies with the Groningen Frailty Indicator [15,36], a short, easy to administer 15-item screening instrument to determine level of frailty (KR-20=.76/.71). The scores range from 0 (not frail) to 15 (severely frail).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frailty was measured in both studies with the Groningen Frailty Indicator [15,36], a short, easy to administer 15-item screening instrument to determine level of frailty (KR-20=.76/.71). The scores range from 0 (not frail) to 15 (severely frail).…”
Section: Methodsmentioning
confidence: 99%
“…Chronological age can be considered as a proxy for all kinds of losses and deficits which occur in aging. These losses, in turn, are related to a decline in SMA [see, e.g., 7,[15][16][17][18][19]. SMA and frailty were also expected to be negatively related.…”
Section: Overview Of the Research And Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that only five instruments included items on all three of these frailty domains: the Frailty Index (FI) or accumulated deficits model [25], Groningen Frailty Indicator (GFI) [57], Clinical Global Impression of Change in Physical Frailty (CGIC-PF) [58], Geriatric Functional Evaluation (GFE) [59], and the Geriatric Functional Evaluation Frailty Index -Comprehensive Geriatric Assessment (FI-CGA) [60]. In addition, the majority of the instruments utilized a dichotomous scoring system (i.e.…”
Section: How Is Frailty Identified or Diagnosed?mentioning
confidence: 99%
“…38 Examples of self-reported questionnaires assessing frailty are: the FRAIL scale, 39 the Groningen Frailty Indicator 40 and the Tilburg Frailty Indicator (TFI) 41 .…”
Section: Frailty Definitions and Measuresmentioning
confidence: 99%